Application of the Problem Posing Approach to Improve Thematic Learning Outcomes of Class V A Students at SD Negeri 014 Rambah - Rinja Efendi; Leni Marlina (STKIP Rokania Pasir Pangaraian, 2022)
This study aims to improve student thematic learning outcomes through the application of the Problem Posing approach. From the initial research data, student learning outcomes are still low, as evidenced by 19 students only 36.85% of students who complete and 63.15% of students do not complete below the KKM 75 that has been set by the school. This type of research is classroom action research conducted in 2 cycles, consisting of planning, implementation, observation and reflection. The subjects of this study were fifth grade students of SD Negeri 014 Rambah. Data collection techniques using tests and observations. The research instrument used observation sheets and learning outcomes test questions. The results showed that after doing research on learning outcomes in the first cycle of meeting 1 obtained 63.16% of students completed, in the first cycle of meeting 2 increased to 79.95% of students who completed, in the second cycle of meeting 1 obtained 84.2% of students completed and at cycle II meeting 2 increased to 89.48% of students completed. It can be concluded that the research on the application of the Problem Posing approach to Improving Thematic Learning Outcomes of Grade V Students of SD Negeri 014 Rambah is said to be successful.